Health Workers Readiness for Implementation of a Mobile Pregnancy Monitoring System in Primary Health Care: A Cross-Sectional Study - Sandra Hakiem Afrizal; Nashrul Hakiem; Dini Oktarina Dwi Handayani; Amy Mardhatillah (Faculty of Computer Science Universitas Indonesia, 2022)
Purpose: The study aims to describe factors related to the readiness of health workers with respect to implementation of a mobile Pregnancy Monitoring System in Primary Health Care (PHC) sites of the South Tangerang District in Banten Province, Indonesia using a socio-technical approach. Methods: A cross-sectional survey design was used among respondents who were involved during the antenatal care process. The participants (n=210) completed the questionnaire that measured information needs regarding the socio-technical aspect of readiness and factors affecting the readiness. The data was analysed using logistic regression analysis. Result: The findings of this study showed that the majority of the health workers who were involved in the antenatal care process were ready to implement the mobile pregnancy monitoring system. Having social media (P= .013) and willingness (P= .007) to be involved in IT implementation are associated with IT readiness, while there is no significant association between demographic factors to the readiness of the health workers. Conclusion: Since there is no connectivity between the demographic factors to readiness, thus the supportive factors such as having a social media and willingness are easier to resolve than inferring from the demographic factors.